Pharmacokinetic evaluation of cabozantinib for the treatment of thyroid cancer. (April 2013) - Karras, Spyridon; Pontikides, Nikolaos; Krassas, Gerasimos E
<x xml:space="preserve">Abstract</x> Introduction: Conventional treatment modalities for thyroid cancer lead to complete remission in only one-third of patients with distant metastases. On the other hand, medullary thyroid cancer (MTC) and anaplastic thyroid cancer (ATC), although rare, are responsible for a significant percentage of thyroid cancer-related deaths. New treatments are needed to treat such patients Areas covered: The aim of this review is to provide the latest information on <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=cabozantinib&logicalOpe1=OR&field2=articletitle&text2=cabozantinib&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">cabozantinib (CBZ), a new tyrosine kinase inhibitor (TKI) that is currently used mainly as a treatment of MTC. The authors collated data that were retrieved from a PubMed literature search. Expert opinion: CBZ targets multiple cell-signaling pathways involved in the molecular pathogenesis of thyroid cancer. These are namely VEGF receptor-2, hepatocyte growth factor receptor and rearranged during transfection receptor. Furthermore, it is a drug which may be used in cases where conventional therapies (mainly for MTC) are proved ineffective or have shown poor results with a good outcome. CBZ may also be administered alone or in combination with other drugs of the same family.